MIMICRY IN POSTCOLONIAL NIGERIAN LITERATURE: A SOCIO-POLITICAL ANALYSIS OF CHIMAMANDA NGOZI ADICHIE’S AMERICANAH (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This study examines the role of mimicry in selected postcolonial Nigerian Literature. The work contends that mimicry occurs in postcolonial Nigerian society as a result of cultural interaction with the British culture during the colonial period. The outcome of this cultural interaction gives birth to a new culture in postcolonial Nigerian society, leaving postcolonial Nigerians struggling to uphold two cultures. This research highlights the problem of identity crisis among the postcolonial Nigerians through assimilation of western culture and how they are perceived by their Western counterparts as the 'other'. In discussing ChimamandaNgozi Adichie's Americanah as Nigerian Postcolonial Literature, this study employs postcolonial literary theory as theoretical framework for the evaluation of how the characters in the selected Nigerian novel handle the issues of mimicry in the postcolonial era, whether they maintain their former identity before colonisation or incorporate their former identity and Western culture together to achieve a balance. However, the study finds out that it is impossible for postcolonial Nigerians to maintain their former identity because their culture has evolved and its authenticity has been lost due to their interaction with the British society.
Keywords: Mimicry,Colonisation,Postcolonialism,NigerianLiterature